2020
DOI: 10.1111/ppl.13237
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 24‐epibrassinolide on plant growth, antioxidants defense system, and endogenous hormones in two wheat varieties under drought stress

Abstract: Drought stress is a major limitation in enhancing agricultural productivity to fulfill the food demand for the world's population. Fertigation of plants with a variety of biochemicals is being used to create drought resistance in wheat; however, the previous work has been limited in addressing these issues in plants at different growth stages.Therefore, a greenhouse study was conducted to ameliorate the drought stress in two wheat varieties (Chakwal-50 and Faisalabad-2008) by foliar application of 24-epibrass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(64 citation statements)
references
References 68 publications
(101 reference statements)
1
50
0
Order By: Relevance
“…To scavenge the higher production of MDA and H 2 O 2 , the antioxidant defense mechanism (SOD, POD, CAT, and APX) is stimulated in plants [54,55]. In a recent study, Khan et al [56] revealed that EBL significantly increased plant growth and triggered the antioxidant defense system in wheat plants against drought stress. Similarly, Rattan et al [57] reported that EBL alleviated salt stress in maize seedlings by regulating the antioxidant enzyme activities.…”
Section: Ebl Enhanced Antioxidant Activity To Mitigate Cr Toxicitymentioning
confidence: 99%
“…To scavenge the higher production of MDA and H 2 O 2 , the antioxidant defense mechanism (SOD, POD, CAT, and APX) is stimulated in plants [54,55]. In a recent study, Khan et al [56] revealed that EBL significantly increased plant growth and triggered the antioxidant defense system in wheat plants against drought stress. Similarly, Rattan et al [57] reported that EBL alleviated salt stress in maize seedlings by regulating the antioxidant enzyme activities.…”
Section: Ebl Enhanced Antioxidant Activity To Mitigate Cr Toxicitymentioning
confidence: 99%
“…Various reports claim that the application of PGPR for sustainable improvements in nutrients and the health of soil and plants [ 4 , 9 , 10 , 11 ]. PGPR are known to produce a wide variety of plant growth-promoting traits that include siderophores [ 10 , 11 ], phytohormones [ 12 , 13 ], hydrolytic enzymes [ 14 ], exopolysaccharide [ 15 , 16 , 17 ], stress-tolerant metabolites [ 18 , 19 , 20 , 21 ], and phosphate solubilization [ 22 , 23 ], etc. PGPR through these metabolites promotes seed germination, root and shoot growth, the level of soil and plant nutrients [ 13 , 21 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…PGPR are known to produce a wide variety of plant growth-promoting traits that include siderophores [ 10 , 11 ], phytohormones [ 12 , 13 ], hydrolytic enzymes [ 14 ], exopolysaccharide [ 15 , 16 , 17 ], stress-tolerant metabolites [ 18 , 19 , 20 , 21 ], and phosphate solubilization [ 22 , 23 ], etc. PGPR through these metabolites promotes seed germination, root and shoot growth, the level of soil and plant nutrients [ 13 , 21 , 24 ]. The beneficial effects of PGPR are sometimes not obtained due to various reasons such as the production of a limited number of plant growth-promoting (PGP) traits, competition with the native soil microflora, less root colonization, and sensitivity to biotic and abiotic stresses [ 2 , 3 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Application of PGPR offers numerous advantages, in terms of plant growth promotion through the secretion of various plant beneficial metabolites [ 12 ], increase in soil fertility [ 13 ], improved drought tolerance in plants through the production of exopolysaccharides and osmolytes [ 1 , 14 , 15 ], protection of plants from pathogens through the production of antibiotics, hydrogen cyanide, hydrolytic enzymes, etc. [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%